2020
DOI: 10.2147/amep.s259557
|View full text |Cite
|
Sign up to set email alerts
|

<p>Perceived Stress Among Iranian Nursing Students in a Clinical Learning Environment: A Cross-Sectional Study</p>

Abstract: Background Nursing students experience a high level of stress in clinical settings. This study aimed to investigate the stress perceived by Iranian nursing students in the clinical learning environment and its relationship with the characteristics of students. Methods In this cross-sectional study, 430 nursing students who had passed at least 1 clinical training unit were recruited from universities in the Southeast of Iran using the census method. Data were collected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…Nursing students with a greater sense of professional identity may have stronger motivations to learn and adapt to the clinical environment more quickly, so their stress levels during the clinical practicum are lower [ 32 ]. Moreover, it has been found that students who choose the nursing profession voluntarily have higher self-confidence, optimism, and a higher sense of professional gain and require less social support [ 35 , 36 ]. Therefore, they experienced lower stress levels than nursing students who did not voluntarily choose the nursing profession.…”
Section: Discussionmentioning
confidence: 99%
“…Nursing students with a greater sense of professional identity may have stronger motivations to learn and adapt to the clinical environment more quickly, so their stress levels during the clinical practicum are lower [ 32 ]. Moreover, it has been found that students who choose the nursing profession voluntarily have higher self-confidence, optimism, and a higher sense of professional gain and require less social support [ 35 , 36 ]. Therefore, they experienced lower stress levels than nursing students who did not voluntarily choose the nursing profession.…”
Section: Discussionmentioning
confidence: 99%
“…Eighty-five complete pieces were eliminated from these, such as unable to obtain the complete text, duplicate content or incomplete data, inconsistent research object and content, and noncross-sectional research type. Finally, 27 studies [16–42] met the inclusion criteria in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…There were 17 high stress level studies. [17–26,28,30,32,34,36,41,42] Meta analysis of random-effects model showed that the prevalence of low, medium and high level of stress before 2010 were 0.22% [0.22 to 0.22], 0.42% [0.42 to 0.42], 0.02% [0.02 to 0.02], respectively. After 2010, the prevalence of low, medium and high level of stress were 0.25 [0.25 to 0.25], 0.35 [0.35 to 0.35], 0.15 [0.15 to 0.15] respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The nursing staff in a clinical environment and teaching staff found to trigger stress among nursing students as well (Waled & Badria, 2019). Limited clinical competence of teaching staff and inappropriate conduct of instructors have a great influence on stress in nursing students (Rafati et al, 2020). Thus, it should be considered that stress caused by educators can end up with negative learning experiences and a lack of motivation among students (Aşçı et al, 2015).…”
Section: Discussionmentioning
confidence: 99%